PENJUALAN SARUNG NGGOLI TENUN BIMA SECARA ONLINE DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Asfin Waraihan; Husnatul Mahmudah; Sri Wahyunti (I-Economics: A Research Journal on Islamic Economics)
This study aims to examine how efforts to develop online sales of Nggoli sarongs admitted by UMKM business actors in Sangiang Village, Wera District, Bima Regency. This research was carried out using a qualitative method with the type of field research to obtain accurate and contextual data. Nggoli sarongs are one type of traditional Bima woven fabric that is quite in demand. The development of information and communication technology has opened new opportunities for the development of online sales of bima woven Nggoli sarongs. Since the Covid-19 pandemic, most traditional factory weavers in Sangiang Village have implemented online sales through social media. By utilizing online sales, nggoli sarongs can be reached wide community. In this study, the researcher focuses on efforts to develop online sales of Nggoli sarongs, especially by women business groups. Data collection is carried out through observation, in-depth interviews and documentation. The results of the study show that (1) there is a significant increase by selling online using the Facebook application. Online sales of Nggoli sarongs have increased sales by 95% and have started to send their merchandise outside the Bima area. (2) Islamic economic views on the online sale of Bima woven sarongs. In the online sale of nggoli woven sarongs, it was found that there are elements of trust, responsibility, fairness and transparency. This is in accordance with the principles of buying and selling in Islam. Such a form of muamalah is allowed if it does not contain elements that are prohibited by Islam, such as usury, tyranny, fraud, and monopoly